2014
DOI: 10.1111/jfpp.12265
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Oxidative Stability of Whey Butter through Almond (P runus dulcis ) Peel Extract

Abstract: Whey butter is characterized with higher concentration of unsaturated fatty acids; the autoxidation of unsaturated fatty acids limits the shelf life of whey butter. We investigated the effect of almond peel extract on oxidative stabilization of whey butter at refrigeration temperature as the butter is put at refrigeration temperature in supermarkets for sale. Whey butter was added with 100 (T1), 200 (T2), 300 (T3) and 400 (T4) ppm concentrations of ethanolic almond peel extract, compared with a control, stored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
39
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 22 publications
(29 reference statements)
4
39
2
Order By: Relevance
“…Fatty acid profile was strongly connected with peroxide value and determination frequencies showing extensive breakdown of unsaturated fatty acids showed higher peroxide value [51]. Nadeem et al [33] reported that fatty acid profile of butter oil significantly changed in the storage period. Fatty acid profile of butter manufactured from low melting point fractions changed during the extended storage period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fatty acid profile was strongly connected with peroxide value and determination frequencies showing extensive breakdown of unsaturated fatty acids showed higher peroxide value [51]. Nadeem et al [33] reported that fatty acid profile of butter oil significantly changed in the storage period. Fatty acid profile of butter manufactured from low melting point fractions changed during the extended storage period.…”
Section: Discussionmentioning
confidence: 99%
“…For the assessment of antioxidant status of complex food substrates, DPPH free radical scavenging activity is widely used. For the assessment of antioxidant capacity of whey butter, margarine and cheddar cheese, DPPH free radical scavenging assay was used [33][34][35]. Buffalo milk has higher content of biochemical compounds having antioxidant capacity e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the garlic addition increased, the titratable acidity values increased. This increase has a detected effect on the quality of the product during storage time, mainly regarding sensorial characteristics such as color, texture, and odor, which are negatively affected . The natural acidity in milk first comes from casein, phosphate, and citrates then from albumin, globulin, and carbon dioxide.…”
Section: Discussionmentioning
confidence: 99%